Accuracy of intraocular lens power calculation formulas in long eyes: a systematic review and meta‐analysis. (24th March 2018) - Wang, Qiwei; Jiang, Wu; Lin, Tiao; Zhu, Yi; Chen, Chuan; Lin, Haotian; Chen, Weirong
Abstract: Importance: Visual outcome after intraocular lens (IOL) implantation in long eyes is considerably affected by IOL power calculation. Various formulas have been designed to achieve an accurate IOL power prediction. However, controversy about the accuracy remains. Background: To evaluate the accuracy of IOL power calculation formulas in long eyes. Design: Meta‐analysis. Participants: Patients with ocular axial length (AL) over 24.5 mm. Methods: A comprehensive search in PubMed, EMBASE, Cochrane Data Base of Systematic Reviews and the Cochrane Central Register of Controlled Trials were conducted by September, 2017. The weighted mean differences of mean absolute errors (MAE) and the odds ratio of percentage of eyes within ±0.50D of prediction error among formulas were analysed. Main Outcomes Measures: Between‐group differences of MAE among formulas. Results: Eleven observational studies, involving 4047 eyes, were enrolled. Six formulas for IOL power calculation were compared: Barrett Universal II, Haigis, Holladay 2, SRK/T, Hoffer Q and Holladay 1. The MAE of Barrett Universal II was statistically lower than that of Holladay 2 (mean difference, MD = −0.04D, P  = 0.0002), SRK/T (MD = −0.05D, P  < 0.00001), Hoffer Q (MD = −0.07D, P  < 0.00001) and Holladay 1 (MD = −0.07D, P  < 0.00001). Barrett Universal II yielded significantly higher percentage of eyes within ±0.50D of the prediction error than the other formulas. The heterogeneity was minimized through dividing eyes into two groups by the AL of 26 mm. Conclusions and Relevance: This study demonstrates the superiority of Barrett Universal II over Holladay 2, SRK/T, Hoffer Q and Holladay 1 in predicting IOL power in long eyes.